Nemaline myopathy diagnosed in two young Border collies in formalin‐fixed paraffin‐embedded muscle samples using conventional stains. Issue 4 (6th December 2018) - Dettwiler, Martina; Sydler, Titus; Klausmann, Stefanie; Beckmann, Katrin; Hilbe, Monika
Abstract : Nemaline myopathy (NM) is a congenital neuromuscular disorder with heterogeneous clinical signs such as muscle weakness, affecting humans, seldom dogs and cats. For human NM, several causative gene mutations have been identified. The hallmark of this disease is the presence of sarcoplasmic inclusions (nemaline rods) in skeletal muscle fibres, which can be visualised in sections of muscle specimens. Ultrastructurally, an enlargement and streaming of the Z lines can be detected. Here, the case of two 10‐week‐old female Border collie littermates with progressive gait dysfunction, muscle stiffness and exercise intolerance, which were euthanased because of poor prognosis, is described. Histology of formalin‐fixed paraffin‐embedded muscle samples revealed sarcoplasmic rods visible in tissue sections stained with haematoxylin and eosin, the Gomori trichrome and the phosphotungstic acid haematoxylin stain. In electron microscopy, the rods were confirmed as streaming of the Z lines. Therefore, a congenital NM was diagnosed.